2010
DOI: 10.1021/jf904228e
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation Induced Enhancement in Isoflavones, Total Phenol, Anthocyanin and Antioxidant Properties of Varying Seed Coat Colored Soybean

Abstract: Three Indian soybean genotypes, namely, Kalitur, Hara soya and NRC37 with black, green and yellow colored seed coat respectively were gamma irradiated at a dose of 0.5, 2.0, and 5.0 kGy. The total isoflavones and total phenol content (TPC) in all the genotypes increased significantly at a dose of 0.5 and 2 kGy respectively. The anthocyanin content was high in Kalitur, while other genotypes showed no detectable amounts of it. The hydroxyl radical scavenging activity (HRSA), DPPH free radical scavenging activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 24 publications
6
26
1
4
Order By: Relevance
“…An increase in antioxidant capacity compared to control was observed for cultivars BRS-213, BRS-258 and Embrapa-48 irradiated with 2 kGy (4.73%), 4 kGy (1.64%) and 8 kGy (9.06%), respectively (Table 1). Although this increase in antioxidant capacity was not significant, these results agree with Dixit et al [2] who showed that irradiation with doses of 0.5 and 2 kGy induced a progressive increase in the antioxidant capacity of the three soybean cultivars, while a decrease was observed at a dose of 5 kGy. Similarly, Popović et al [1] observed a gradual increase in antioxidant capacity when they submitted a Serbian soybean cultivar to gamma radiation with doses of 1, 2, 4 and 10 kGy.…”
Section: Physicochemical Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…An increase in antioxidant capacity compared to control was observed for cultivars BRS-213, BRS-258 and Embrapa-48 irradiated with 2 kGy (4.73%), 4 kGy (1.64%) and 8 kGy (9.06%), respectively (Table 1). Although this increase in antioxidant capacity was not significant, these results agree with Dixit et al [2] who showed that irradiation with doses of 0.5 and 2 kGy induced a progressive increase in the antioxidant capacity of the three soybean cultivars, while a decrease was observed at a dose of 5 kGy. Similarly, Popović et al [1] observed a gradual increase in antioxidant capacity when they submitted a Serbian soybean cultivar to gamma radiation with doses of 1, 2, 4 and 10 kGy.…”
Section: Physicochemical Analysissupporting
confidence: 91%
“…This characteristic is mainly attributed to the presence of proteins and phytochemicals (isoflavones, tocopherol, phytosterols), compounds with an elevated antioxidant potential that prevent the formation of reactive oxygen species. Soy products are investigated as foods to reduce the risk of breast and prostate cancer, osteoporosis, cardiovascular diseases and postmenopausal symptoms, as well as serum cholesterol and triglycerides levels [2].…”
Section: Introductionmentioning
confidence: 99%
“…This recovery may have been due to the generation of certain antioxidants, because irradiation has produced antioxidants at a specific dosage. 22) The reduced DPPH radical scavenging activity of soybean oil irradiated with rays ( Fig. 4B and C) was probably the result of irradiation-induced losses of both unsaturated fatty acids (Table 3) and carotenoids, 23) both of which are known to scavenge DPPH radicals.…”
Section: Effects Of Irradiation On the Radical Scavenging Activities mentioning
confidence: 94%
“…[48]. According to the authors, gamma-irradiated soybean genotypes showed an increase in antioxidant constituents and antioxidant properties at low doses of 0.5 kGy and 2.0 kGy, while the antioxidant effects of soy seeds either decreased or remained constant at a higher dose of 5.0 kGy.…”
Section: Resultsmentioning
confidence: 99%